1998
DOI: 10.1016/s0741-5214(98)70228-9
|View full text |Cite
|
Sign up to set email alerts
|

A ten-year experience of Brescia-Cimino arteriovenous fistula in children: Technical evolution and refinements

Abstract: We emphasize the following two conclusions: first, microsurgery is essential to create AVFs with good results in children as well as in adult patients; and second, the results improved after the adoption of an upper-arm exsanguination and ischemia (pressure range, 400 mm Hg to 600 mm Hg) that avoided spasm of the vessels with a final 35% reduction in surgical time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 6 publications
3
60
0
2
Order By: Relevance
“…11,12 Despite the described advantages of this technique, mainly the avoidance of arterial spasm, minimal hemostasis, safer dissection of the main vessels, and the absence of clamping, we are not accustomed to using such devices. Therefore, we preferred to dissect the vessels with minimal trauma and ligate all the small collateral branches.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Despite the described advantages of this technique, mainly the avoidance of arterial spasm, minimal hemostasis, safer dissection of the main vessels, and the absence of clamping, we are not accustomed to using such devices. Therefore, we preferred to dissect the vessels with minimal trauma and ligate all the small collateral branches.…”
Section: Discussionmentioning
confidence: 99%
“…13 The BresciaCimino fistula provided vascular access with a longterm patency rate and a low incidence of complications. 14 Wander et al reported on the first successful creation of AVFs in children in 1970. 15 In 1973, Broyer et al reported 54% success in creating distal fistulae in children who weighed less than 20 kg.…”
Section: Resultsmentioning
confidence: 99%
“…6 In 2003, Bourquelot et al 9 stated that the benefits of microsurgery in children were reported by Yazbeck and O'Regan in 1984, 21 Sanabia et al in 1993, 22 and Bagolan et al in 1998. 14 Bourquelot et al further stated that ''microsurgery is mandatory for creation of AVFs, the best form of angioaccess for children treated by hemodialysis or requiring repeated access to blood in various non-renal diseases.'' 9 Tannuri and Tannuri also espoused the benefits of microsurgical techniques in creating AVFs for hemodialysis in children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly after that, Brescia and Cimino first described the AVF, which is the longest lasting hemodialysis access method used to date (Bagolan et al, 1998). Three types of hemodialysis access methods have been recommended by the NFK/KDOQI (2006), including autogenous AVF, a prosthetic vascular graft, and a central venous catheter.…”
Section: Discussionmentioning
confidence: 99%